Fire-sale spillovers and systemic risk - Fernando Duarte; Thomas M. Eisenbach (Federal Reserve Bank of New York, 2013)
We construct a new systemic risk measure that quantifies vulnerability to fire-sale spillovers using detailed regulatory balance sheet data for U.S. commercial banks and repo market data for broker-dealers. Even for moderate shocks in normal times, fire-sale externalities can be substantial. For commercial banks, a 1 percent exogenous shock to assets in 2013:Q1 produces fire-sale externalities equal to 21 percent of system capital. For broker-dealers, a 0.1 percent shock to assets in August 2013 generates spillover losses equivalent to almost 6 percent of system capital. Externalities during the last financial crisis are between two and three times larger. Our systemic risk measure reaches a peak in the fall of 2007 but shows a notable increase starting in 2004, ahead of many other systemic risk indicators. Although the largest banks and brokerdealers produce - and are victims of - most of the externalities, leverage and linkages of financial institutions also play important roles.
Keywords: G01; G10; G18; G20; G21; G23; G28; G32; 330; systemic risk; fire-sale externalities; leverage; concentration; bank holding company; tri-party repo market